Preparation method of high-compaction-density lithium iron phosphate positive electrode material
By using the preparation method of high-pressure density positive electrode material in lithium iron phosphate batteries, and using wet grinding and self-propagation high-temperature synthesis technology, the problem of limited space for improving energy density of lithium iron phosphate batteries is solved, and the effect of significantly improving energy density and range is achieved.
Patent Information
- Application Number
- CN202411951327.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
The energy density of existing lithium iron phosphate batteries is close to the theoretical value, and the room for improvement is extremely limited, making it difficult to charge and discharge more electricity under a certain volume.
The preparation method of high-pressure density lithium iron phosphate positive electrode material is adopted, and the compaction density and reaction activity of the material are improved by combining wet grinding and self-propagation high-temperature synthesis. Specific steps include wet grinding of the mixture, spray drying, molding and self-propagation calcination.
It significantly improves the energy density of lithium-ion batteries, increases the range of electric vehicles, and reduces the battery weight, achieving the purpose of increasing volumetric energy density.
Smart Images

Figure CN119683597A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a high compaction density lithium iron phosphate positive electrode material. Background Art
[0002] With the development of science and technology, the demand for energy in modern society has increased dramatically, while the reserves of non-renewable energy such as coal, oil and natural gas are limited. In order to achieve sustainable development, the country is vigorously developing clean energy such as wind power, hydropower, solar power generation and green transportation such as new energy vehicles while studying technologies and equipment to improve energy utilization. The lithium iron phosphate battery industry has developed significantly with the rise of the new energy vehicle industry. Under the influence of factors such as changes in new energy vehicle subsidy policies, prominent cost advantages, and continuous performance improvements, the penetration rate of lithium iron phosphate batteries reached 51.7% in 2021, successfully surpassing ternary lithium batteries to become a mainstream product. In May 2024, the installed capacity of lithium iron phosphate batteries was 29.5GWh, a year-on-year increase of 54.1%, accounting for 74.0% of the total installed capacity, and the market share of lithium iron phosphate batteries successfully exceeded the 70% mark. In 2023, the production capacity of iron phosphate and lithium iron phosphate continued to be released. By the end of 2023, China's iron phosphate production capacity reached 3.619 million tons and lithium iron phosphate production capacity reached 3.417 million tons.
[0003] The technical routes and material systems adopted by major manufacturers in the market are basically the same. They all use lithium source, phosphorus source and iron source as the main materials. They only differ in the synthesis method (solid phase method, liquid phase method) and specific material composition (ferric phosphate, ferrous oxalate, ferric nitrate, iron oxide, etc.). The solid phase method has relatively simple process steps, low cost and easy industrialization. Lithium iron phosphate is often synthesized using this method. High temperature solid phase method and carbon thermal reduction method are the two most commonly used solid phase methods. Although the liquid phase method can better control the crystal form and particle size of the material, it has high requirements for the production environment and equipment and complex processes. Its industrialization is more difficult than the solid phase synthesis method. The main methods include hydrothermal method and coprecipitation method.
[0004] With the development of the new energy industry, users have put forward higher requirements for lithium iron phosphate batteries. Blade batteries, CTP and other technologies have effectively improved the system integration efficiency of lithium iron phosphate batteries, but the energy density "ceiling" of lithium iron phosphate always exists. Users have proposed that more electricity can be charged and discharged under a certain volume, but the energy density of lithium iron phosphate batteries is close to the theoretical value, and there is extremely limited room for improvement. Summary of the invention
[0005] The present invention aims to provide a method for preparing a high compaction density lithium iron phosphate positive electrode material to improve the volume energy density of the battery.
[0006] To achieve the above object, the present invention adopts the following technical solution: a method for preparing a high compaction density lithium iron phosphate positive electrode material, comprising the following steps:
[0007] Step 1: Mix and grind iron phosphate, lithium carbonate, a carbon source, a dispersant and deionized water to obtain a mixed slurry, and then wet-grind the mixed slurry;
[0008] Step 2: spray drying the mixed slurry after wet grinding reaction to obtain lithium iron phosphate precursor powder, and molding the lithium iron phosphate precursor powder to obtain a pre-calcined material;
[0009] Step 3: subject the material to self-propagating calcination, and obtain the finished lithium iron phosphate product after cooling.
[0010] Preferably, as an improvement, in step one, the carbon source is at least one of sucrose, glucose, fructose, starch, activated carbon, and carbon black; the dispersant is at least one of polyethylene glycol, citric acid, polyvinyl alcohol, ethylenediaminetetraacetic acid, hexadecyltrimethylammonium bromide, and sodium octylbenzenesulfonate.
[0011] Preferably, as an improvement, in step one, the mass ratio of iron phosphate, lithium carbonate and carbon source is 1:1.03:0.1.
[0012] Preferably, as an improvement, in step one, the grinding operation is sand grinding, the sand grinding temperature is 10-15°C, the sand grinding time is 1-2h, and the slurry particle size D50 after sand grinding is ≤1μm.
[0013] Preferably, as an improvement, in step one, the wet grinding intensity is 3000-13000 rpm, and the wet grinding circulation volume is 1-2 L / min.
[0014] Preferably, as an improvement, in step 2, the spray drying is 0.6-1.2 MPa, the spray temperature is 150-190° C., and the solid content of the slurry is 10-50%.
[0015] Preferably, as an improvement, in step 2, the molding pressure is 5-15 MPa.
[0016] Preferably, as an improvement, in step three, the calcination temperature is 550-750° C., and the calcination time is 4 hours.
[0017] Preferably, as an improvement, in step three, the heating rate is 2°C / min.
[0018] The principle and advantage of this solution are: in actual application, in this technical solution, the problems existing in the prior art are solved by cleverly utilizing a method combining wet grinding and self-propagating high temperature synthesis as a means of crystallization strengthening. In the process of wet grinding, it can play the role of mixing, crushing, oxygenation and activation, resulting in changes in the crystal state and chemical changes. In the process of wet grinding, the solid mixture will have violent collisions and friction with the grinding body, rotor and other machinery. The particles will be broken during the collision, the particle size will be reduced, and the particles will be uniform. It is very easy to cause the powder lattice to be distorted and deformed, so that the powder body energy is increased, which is beneficial to improve the reaction activity of the reactants. At the same time, during use, the mixture will react under some extreme conditions, causing the structure of the reactants to change. The wet-grinded materials have a significant effect on the shrinkage and densification process of sintering. In addition, the self-propagating calcination process can make the materials calcined more fully, thereby achieving the effect of increasing the compaction density. Finally, this "activation phenomenon" can be used to promote the rapid growth of some grains during the sintering process, which can easily cause the "coarse inclusion" phenomenon, resulting in uneven particle distribution, and thus making the particle size in the product have a good grading relationship, and the compaction density of the product can be further improved.
[0019] In summary, the beneficial effects of this technical solution are:
[0020] 1. This technical solution innovatively uses a combination of wet grinding and self-propagating high temperature synthesis. The front end uses a wet grinding method to control the particle size activity and uniformity between particles. Finally, self-propagating sintering is used during the calcination process to improve the shrinkage and density of the particles. At the same time, the treated material can also increase the particle grading effect, thereby achieving an increase in the compaction density index of lithium iron phosphate, and the compaction density is ≥2.6g / cm 3 .
[0021] 2. This technical solution has a simple process flow and stable control. It can improve the compaction density while maintaining a high battery capacity level, which can significantly improve the energy density of lithium-ion batteries. It is an important means to increase the cruising range of electric vehicles and reduce battery weight. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an appearance morphology diagram of the lithium iron phosphate positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.
[0024] Program Overview:
[0025] A method for preparing a high-density lithium iron phosphate positive electrode material comprises the following steps:
[0026] Step 1, wet grinding of ingredients: mix iron phosphate, lithium carbonate, carbon source and deionized water in a certain mass ratio (iron phosphate: lithium carbonate: carbon source = 1: 1.03: 0.1), and add dispersant for batching. The carbon source is at least one of sucrose, glucose, fructose, starch, activated carbon, and carbon black; the dispersant is at least one of polyethylene glycol, citric acid, polyvinyl alcohol, ethylenediaminetetraacetic acid, hexadecyltrimethylammonium bromide, and sodium octylbenzenesulfonate; the sanding time is 1-2h, the sanding temperature is set to 10-15°C, and the slurry particle size D50 after sanding is ≤1μm. The sanding liquid obtained in the above steps is mixed and passed into the wet grinding pump, the wet grinding intensity is set to 3000-13000rpm, and the wet grinding circulation volume is set to 1-2L / min to carry out wet grinding reaction.
[0027] Step 2, dry briquetting: The wet-milled mixed solution (solid content of 10-50%) after wet-milling reaction is directly spray-dried. First, set the inlet temperature of the spray dryer to 150-190°C, the spray pressure to 0.6-1.2Mpa, the fan frequency to 50Hz, and the peristaltic pump speed to 25r / min. After starting up, turn on the fan, air compressor, and heater. When the inlet temperature reaches 130°C, turn on the peristaltic pump to spray. After the material is sprayed, add 100mL of distilled water to continue spraying to clean up the material remaining in the pipeline. When completed, turn off the peristaltic pump and heater first. When the inlet temperature drops below 60°C, turn off the fan and air compressor, and then turn off the machine to obtain the dried lithium iron phosphate precursor powder. Then put the lithium iron phosphate precursor powder into a pressure mold, set the die pressure to 5-15Mpa, and shape the pre-calcined material into a cylindrical shape under a high-strength press.
[0028] Step 3, self-propagating calcination: Place the above materials in a tubular furnace and sinter under the protection of argon (heating rate 2°C / min), the calcination temperature is set to 550-750°C, and the calcination time is 4h; after natural cooling, the finished lithium iron phosphate product is obtained.
[0029] Example 1
[0030] A method for preparing a high-density lithium iron phosphate positive electrode material comprises the following steps:
[0031] Step 1, wet grinding of ingredients: Mix iron phosphate, lithium carbonate, glucose and deionized water in a certain mass ratio (iron phosphate: lithium carbonate: carbon source = 1:1.03:0.1), and add polyethylene glycol as a dispersant for mixing. The sand grinding time is set to 1h, and the sand grinding temperature is set to 10°C. The sand grinding liquid obtained in the above steps is mixed and passed into the wet grinding pump, the wet grinding intensity is set to 3000rpm, and the wet grinding circulation volume is set to 1L / min, and the wet grinding reaction is carried out.
[0032] Step 2, dry briquetting: The wet-milled mixed solution (solid content of 10%) after wet-milling reaction is directly spray-dried. First, set the inlet temperature of the spray dryer to 150°C, the spray pressure to 0.6Mpa, the fan frequency to 50Hz, and the peristaltic pump speed to 25r / min. After starting up, turn on the fan, air compressor, and heater. When the inlet temperature reaches 130°C, turn on the peristaltic pump to spray. After the material is sprayed, add 100mL of distilled water to continue spraying to clean up the material remaining in the pipeline. When completed, turn off the peristaltic pump and heater first. When the inlet temperature drops below 60°C, turn off the fan and air compressor, and then turn off the machine. Get the dried lithium iron phosphate precursor powder. Then put the lithium iron phosphate precursor powder in a pressure mold, set the die pressure to 5Mpa, and shape the pre-calcined material into a cylindrical shape under a high-strength press.
[0033] Step 3, self-propagating calcination: The dried pressed sample is placed in a tubular furnace and fired under the protection of argon (heating rate 2°C / min). The calcination temperature is set to 550°C and the calcination time is 4h. After natural cooling, the finished lithium iron phosphate product is obtained.
[0034] Example 2
[0035] A method for preparing a high-density lithium iron phosphate positive electrode material comprises the following steps:
[0036] Step 1, wet grinding of ingredients: Mix iron phosphate, lithium carbonate, glucose and deionized water in a certain mass ratio (iron phosphate: lithium carbonate: carbon source = 1:1.03:0.1), and add polyethylene glycol as a dispersant for mixing. The sand grinding time is set to 1.5h, and the sand grinding temperature is set to 13°C. The sand grinding liquid obtained in the above steps is mixed and passed into the wet grinding pump, the wet grinding intensity is set to 8000rpm, and the wet grinding circulation volume is set to 1.5L / min, and the wet grinding reaction is carried out.
[0037] Step 2, dry briquetting: The wet-milled mixed solution (solid content of 30%) after wet-milling reaction is directly spray-dried. First, set the inlet temperature of the spray dryer to 170°C, the spray pressure to 0.9Mpa, the fan frequency to 50Hz, and the peristaltic pump speed to 25r / min. After starting up, turn on the fan, air compressor, and heater. When the inlet temperature reaches 150°C, turn on the peristaltic pump to spray. After the material is sprayed, add 100mL of distilled water to continue spraying to clean up the material remaining in the pipeline. When completed, turn off the peristaltic pump and heater first. When the inlet temperature drops below 60°C, turn off the fan and air compressor, and then turn off the machine. Get the dried lithium iron phosphate precursor powder. Then put the lithium iron phosphate precursor powder in a pressure mold, set the die pressure to 10Mpa, and shape the pre-calcined material into a cylindrical shape under a high-strength press.
[0038] Step 3, self-propagating calcination: The dried pressed sample is placed in a tubular furnace and fired under the protection of argon (heating rate 2°C / min). The calcination temperature is set to 650°C and the calcination time is 4h. After natural cooling, the finished lithium iron phosphate product is obtained.
[0039] Example 3
[0040] A method for preparing a high-density lithium iron phosphate positive electrode material comprises the following steps:
[0041] Step 1, wet grinding of ingredients: iron phosphate, lithium carbonate, glucose and deionized water are mixed in a certain mass ratio (iron phosphate: lithium carbonate: carbon source = 1:1.03:0.1), and polyethylene glycol is added as a dispersant for mixing. The sand grinding time is set to 2h, and the sand grinding temperature is set to 15°C. The sand grinding liquid obtained in the above steps is mixed and passed into the wet grinding pump, the wet grinding intensity is set to 13000rpm, and the wet grinding circulation volume is set to 2L / min, and the wet grinding reaction is carried out.
[0042] Step 2, dry briquetting: The wet-milled mixed solution (solid content of 50%) after wet-milling reaction is directly spray-dried. First, set the inlet temperature of the spray dryer to 190°C, the spray pressure to 1.2Mpa, the fan frequency to 50Hz, and the peristaltic pump speed to 25r / min. After starting up, turn on the fan, air compressor, and heater. When the inlet temperature reaches 170°C, turn on the peristaltic pump to spray. After the material is sprayed, add 100mL of distilled water to continue spraying to clean up the material remaining in the pipeline. When completed, turn off the peristaltic pump and heater first. When the inlet temperature drops below 60°C, turn off the fan and air compressor, and then turn off the machine. Get the dried lithium iron phosphate precursor powder. Then put the lithium iron phosphate precursor powder in a pressure mold, set the die pressure to 15Mpa, and shape the pre-calcined material into a cylindrical shape under a high-strength press.
[0043] Step 3, self-propagating calcination: The dried pressed sample is placed in a tubular furnace and fired under the protection of argon (heating rate 2°C / min). The calcination temperature is set to 750°C and the calcination time is 4h. After natural cooling, the finished lithium iron phosphate product is obtained.
[0044] Comparative Example 1
[0045] The difference between this comparative example and Example 1 is that in this comparative example, no wet grinding treatment is performed in step 1.
[0046] Comparative Example 2
[0047] The difference between this comparative example and Example 1 is that in this comparative example, the heating rate in step 3 is 1° C. / min.
[0048] Comparative Example 3
[0049] The difference between this comparative example and Example 1 is that in this comparative example, the heating rate in step 3 is 3° C. / min.
[0050] Comparative Example 4
[0051] The difference between this comparative example and Example 1 is that in this comparative example, the calcination temperature in step 3 is 500°C.
[0052] Comparative Example 5
[0053] The difference between this comparative example and Example 1 is that in this comparative example, the calcination temperature in step 3 is 800°C.
[0054] Experimental Example 1 Appearance
[0055] The high compaction density lithium iron phosphate positive electrode material prepared in Example 1 was scanned by electron microscope, and the results were as follows: Figure 1 shown.
[0056] Embodiment 2 Performance Test
[0057] The performance test of the high compaction density lithium iron phosphate positive electrode materials prepared in the above embodiments and comparative examples was carried out. The test method was referred to YS / T 1027-2015 lithium iron phosphate. The test results are shown in Table 1. The results show that the compaction density of the powder in the embodiment of the present invention is large, and the discharge capacity and the first-round discharge efficiency are excellent. The comparative example adopts wet grinding operation, which will lead to a decrease in compaction density and deterioration of discharge performance; in addition, the calcination temperature and rate have a certain influence on the size of iron phosphate particles, which will in turn affect the discharge performance of the material to a certain extent.
[0058] Table 1
[0059] Analyze Project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 <![CDATA[Powder Compaction Density (m 2 / g)]]> 2.60 2.63 2.61 2.42 2.46 2.48 2.37 2.57 0.1C discharge capacity (mAh / g) 157.6 158.4 157.4 150.1 147.2 148.4 158.6 142.4 0.2C discharge capacity (mAh / g) 158.8 157.2 156.8 148.3 145.3 147.6 158.4 141.5 1C discharge capacity (mAh / g) 148.8 146.2 147.4 140.4 136.4 138.2 149.2 132.3 First effect (%) 99.6 98.3 99.3 96.7 96.9 97.3 99.4 94.6
[0060] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a high compaction density lithium iron phosphate positive electrode material, characterized in that: The steps include: Step 1: Mix and grind iron phosphate, lithium carbonate, a carbon source, a dispersant and deionized water to obtain a mixed slurry, and then wet-grind the mixed slurry; Step 2: spray drying the mixed slurry after wet grinding reaction to obtain lithium iron phosphate precursor powder, and molding the lithium iron phosphate precursor powder to obtain a pre-calcined material; Step 3: subject the material to self-propagating calcination, and obtain the finished lithium iron phosphate product after cooling.
2. The method for preparing a high compaction density lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 1, the carbon source is at least one of sucrose, glucose, fructose, starch, activated carbon, and carbon black; the dispersant is at least one of polyethylene glycol, citric acid, polyvinyl alcohol, ethylenediaminetetraacetic acid, hexadecyltrimethylammonium bromide, and sodium octylbenzenesulfonate.
3. The method for preparing a high compaction density lithium iron phosphate positive electrode material according to claim 2, characterized in that: In step 1, the mass ratio of iron phosphate, lithium carbonate and carbon source is 1:1.03:0.
1.
4. The method for preparing a high compaction density lithium iron phosphate positive electrode material according to claim 3, characterized in that: In step 1, the grinding operation is sand grinding, the sand grinding temperature is 10-15° C., the sand grinding time is 1-2 h, and the slurry particle size D50 after sand grinding is ≤1 μm.
5. The method for preparing a high compaction density lithium iron phosphate positive electrode material according to claim 4, characterized in that: In step 1, the wet grinding intensity is 3000-13000rpm, and the wet grinding circulation volume is 1-2L / min.
6. The method for preparing a high compaction density lithium iron phosphate positive electrode material according to claim 5, characterized in that: In step 2, spray drying is performed at 0.6-1.2 MPa, the spray temperature is 150-190° C., and the solid content of the slurry is 10-50%.
7. The method for preparing a high compaction density lithium iron phosphate positive electrode material according to claim 6, characterized in that: In step 2, the molding pressure is 5-15Mpa.
8. The method for preparing a high compaction density lithium iron phosphate positive electrode material according to claim 7, characterized in that: In step 3, the calcination temperature is 550-750° C. and the calcination time is 4 hours.
9. The method for preparing a high compaction density lithium iron phosphate positive electrode material according to claim 8, characterized in that: In step 3, the heating rate is 2°C / min.
Citation Information
Cited By
High-temperature-resistant low-iron-dissolution lithium iron phosphate material as well as preparation method and application thereof
CN120664513A